Field isotopic study of lead fate and compartmentalization in earthworm–soil–metal particle systems for highly polluted soil near Pb recycling factory. (November 2015) - Goix, Sylvaine; Mombo, Stéphane; Schreck, Eva; Pierart, Antoine; Lévêque, Thibaut; Deola, Frédéric; Dumat, Camille
Graphical abstract: Highlights: High Pb content in soils, earthworms and casts decreasing with distance to factory. Anthropogenic Pb inhibits organic matter decomposition through ecotoxicity. No biological Pb isotopic fractionation during earthworm digestion step. Earthworms ingest preferentially anthropogenic Pb sorbed on organic matter. Abstract: Earthworms are important organisms in soil macrofauna and play a key role in soil functionality, and consequently in terrestrial ecotoxicological risk assessments. Because they are frequently observed in soils strongly polluted by metals, the influence of earthworm bioturbation on Pb fate could therefore be studied through the use of Pb isotopes. Total Pb concentrations and isotopic composition ( 206 Pb, 207 Pb and 208 Pb) were then measured in earthworms, casts and bulk soils sampled at different distance from a lead recycling factory. Results showed decreasing Pb concentrations with the distance from the factory whatever the considered matrix (bulk soils, earthworm bodies or cast samples) with higher concentrations in bulk soils than in cast samples. The bivariate plot 208 Pb/ 206 Pb ratios versus 206 Pb/ 207 Pb ratios showed that all samples can be considered as a linear mixing between metallic process particulate matter (PM) and geochemical Pb background. Calculated anthropogenic fraction of Pb varied between approximately 84% and 100%. Based on Pb isotopic signatures, the comparison between casts, earthworms and bulk soils allowed to conclude that earthworms preferentially ingest the anthropogenic lead fraction associated with coarse soil organic matter. Actually, soil organic matter was better correlated with Pb isotopic ratios than with Pb content in soils. The proposed hypothesis is therefore a decrease of soil organic matter turnover due to Pb pollution with consequences on Pb distribution in soils and earthworm exposure. Finally, Pb isotopes analysis constitutes an efficient tool to study the influence of earthworm bioturbation on Pb cycle in polluted soils.